Analyzing the Influence of Dimensions of Customer Based Airline Brand Equity Toward Brand Trust. Case Study of Customer of Citilink - Nathaniel Engelbert Chandra; Esa Theodore Mbouw (Conference Series, 2020)
Indonesia's airline industry has rapidly grown from the past 10 years for both full-service carriers and low-cost carriers. Customers are faced by lots of LCC airlines; these airlines brand performance being independently surveyed by Frontier Research three times a year and awarded with “Top Brand Award”. Therefore, the purpose of this research is to determine the factor that influences Citilink Indonesia brand trust in order to increase their position in Top Brand Award. The model used in this study incorporated Flight Service Quality, Brand Affect, Self-Congruence, Brand Awareness and Brand Association compatibility into Customer-Based Airline Brand Equity as a determinant of Brand Trust. The findings revealed that Flight Service Quality had a significant influence followed by Brand Awareness and Brand Association. However, neither Brand Affect nor Self-Congruence was found to have an influence on Brand Trust. These findings provided implications for management and recommendations to step their Brand Trust.